2016
DOI: 10.1310/hpj5104-296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Corticosteroid Dose on the Incidence of Hyperglycemia in Hospitalized Patients with an Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Study results suggest that a link between larger corticosteroid doses and hyperglycemia incidence may exist, but it requires further study. RESULTS in non-insulin-dependent diabetics provide evidence for increased glucose monitoring upon initiation of corticosteroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“… 16 , 28 However, whether corticosteroid therapy is associated with hyperglycemia in patients with DM during AECOPD remains controversial. Although studies have indicated that corticosteroid therapy increases the risk of hyperglycemia in all individuals with an underlying respiratory disease, 29 , 30 other studies have argued that corticosteroid treatment does not have a significant effect on the HbA1c levels in patients with DM and AECOPD. 31 , 32 As expected, we also found that patients in the high-risk COPD group had a higher rate of developing ARF and were more likely to use corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 28 However, whether corticosteroid therapy is associated with hyperglycemia in patients with DM during AECOPD remains controversial. Although studies have indicated that corticosteroid therapy increases the risk of hyperglycemia in all individuals with an underlying respiratory disease, 29 , 30 other studies have argued that corticosteroid treatment does not have a significant effect on the HbA1c levels in patients with DM and AECOPD. 31 , 32 As expected, we also found that patients in the high-risk COPD group had a higher rate of developing ARF and were more likely to use corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,16,17 This potential difference may be due to the way we determined an increase in blood glucose, which differed compared with other studies. 5,16 The use of a 30% increase from each patient's baseline allowed patients to act as their own reference point, and assess impact of the corticosteroids instead of overall control of diabetes. 8 This potentially provided a more even comparison while including both patients with and without diabetes.…”
Section: Discussionmentioning
confidence: 77%
“…Corticosteroids reduce inflammation, decrease the risk of treatment failure and promote recovery from symptoms [ 9 ]. However, potential side effects are associated with corticosteroid treatment, including increased risk of infections, osteoporosis, adrenal insufficiency, venous thromboembolisms and hyperglycaemia [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, minimising the accumulated dose of corticosteroids while effectively treating exacerbations is very important.…”
Section: Decreasing Exposure To Corticosteroid Treatmentmentioning
confidence: 99%